Risk Factors for Adenoid Hypertrophy in Patients Twelve Year and Older - Mahafza, Tareq; Al-Ananbeh, Lubna; Zuriekat, Margaret; Obeid, Zeinab; Albdour, Eshraq; Shaheen, Majd; Rawashdeh, Majd; Mahafza, Naseem (Jordan Medical Journal, 2023)
Background: The adenoids are part of Waldeyer’s ring of lymphoid tissue and when hypertrophied they cause many symptoms, e.g., snoring. They hypertrophy physiologically in children between the ages of 6 and 10 years, and then atrophy by the age of 16 years. Objectives: The aim of this study was to reveal the risk factors and clinical patterns associated with adenoid hypertrophy in patients aged over 12 years. Methods: We studied 130 patients aged over 12 who had undergone an adenoidectomy between January 2016 to January 2021. Patients were evaluated in the Department of Otorhinolaryngology and Head and Neck Surgery at Jordan University Hospital, Amman, Jordan. Some patients were accessed using medical records and their data were collected by telephone. Results: Of the 130 patients, 81 were male and 49 were female, with a mean age of 19.68 years. Snoring was the most common presenting symptom (81.5%), followed by nasal obstruction (75.4%) and mouth breathing (71.5%). The most common associated risk factor was septal deviation (44.6%), and then passive smoking (40.8 %), allergic rhinitis (38.5%), and pollution (38.5%). Conclusion: There are multiple suspected risk factors for adenoid hypertrophy in patients aged over 12 years. In our study, septal deviation was the most common associated factor, followed by passive smoking, allergic rhinitis and pollution. Snoring was the most common presenting symptom, followed by nasal obstruction.